2017
DOI: 10.1177/000313481708300220
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Mortality Associated with Temporary Abdominal Closure Techniques: A Systematic Review and Meta-Analysis

Abstract: Temporary abdominal closure (TAC) techniques are routinely used in the open abdomen. Ideally, they should prevent evisceration, aid in removal of unwanted fluid from the peritoneal cavity, facilitate in achieving safe definitive fascial closure, as well as prevent the development of intra-abdominal complications. TAC techniques used in the open abdomen were compared with negative pressure wound therapy (NPWT) to identify which was superior. A systematic review was conducted using the Preferred Reporting Items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 198 publications
1
47
0
4
Order By: Relevance
“…Basierend auf der bereits seit vielen Jahren etablierten NPWT [16][17][18][19][20][21][22][23][24], die meist als Methode der temporären Weichteildeckung zur Wundbettpräparation in der Überbrückung bis zu einem abschließenden Wundverschluss eingesetzt wird, wurde die Modalität einer zusätzlichen Instillationstherapie mit steuerbarer Einwirkzeit entwickelt.…”
Section: Vakuumtherapieunclassified
“…Basierend auf der bereits seit vielen Jahren etablierten NPWT [16][17][18][19][20][21][22][23][24], die meist als Methode der temporären Weichteildeckung zur Wundbettpräparation in der Überbrückung bis zu einem abschließenden Wundverschluss eingesetzt wird, wurde die Modalität einer zusätzlichen Instillationstherapie mit steuerbarer Einwirkzeit entwickelt.…”
Section: Vakuumtherapieunclassified
“…Literature retrieval found a meta-analysis involving only randomized controlled trials showed that NPWT with continuous fascial closure was superior to NPWT alone for definitive fascial closure. [14] Therefore, it was concluded that NPWT does effectiveness in deal with OA.…”
Section: Discussionmentioning
confidence: 99%
“…In two recent systematic reviews with metaanalyses [27,28] on OA and TAC techniques, NPWT with continuous fascial traction was associated with a higher delayed fascial closure rate and lower entero-atmospheric fistula formation rate compared to NPWT alone. This emphasizes the importance of having an effective method to close the abdomen as quickly as possible to reduce the risk of complications associated with OA therapy.…”
Section: Open Abdomen Therapy With Negative Pressure Wound Therapy Onmentioning
confidence: 98%